Effects of Carboxyl or Amino Group Modified InP/ZnS Nanoparticles Toward Simulated Lung Surfactant Membrane - Wang, Juan; Feng, Shun; Liu, Jie; Liu, Rui-Lin (Frontiers in Bioengineering and Biotechnology, 2021)
Quantum dots (QDs) as a promising optical probe have been widely used for in vivo biomedical imaging, especially enormous efforts recently have been focused on the potential toxicity of QDs to human body. The toxicological effects of the representative InP/ZnS QDs as a cadmium-free emitter are still in the early stage and have not been fully unveiled. In this study, the DPPC/DPPG mixed monolayer was used to simulate the lung surfactant monolayer. The InP/ZnS-COOH QDs and InP/ZnS-NH2 QDs were introduced to simulate the lung surfactant membrane’s environment in the presence of InP/ZnS QDs. The effects of InP/ZnS QDs on the surface behavior, elastic modulus and stability of DPPC/DPPG mixed monolayer were explored by the surface pressure-mean molecular area isotherms and surface pressure-time curves. The images observed by Brewster angle microscope and atomic force microscope showed the InP/ZnS QDs affected the morphology of monolayer. The results further demonstrated that the InP/ZnS QDs coated with different surface groups can obviously adjust the mean molecular area, elastic modulus, stability and microstructure of DPPC/DPPG mixed monolayer. Overall, this work provided a useful information for in-depth understanding the effects of the -COOH or -NH2 group coated InP/ZnS QDs on surface of lung surfactant membrane, which will help scientists to further study the physiological toxicity of InP/ZnS QDs to lung health.